Pengaruh Kombinasi Pupuk NPK dan Mikoriza Terhadap Pertumbuhan dan Hasil Kedelai (Glycine max (L.) Merril) Varietas Devon 1 - Zaenul Maknun; Dyah Weny Respatie; Haviah Hafidhotul Ilmiah (Vegetalika, 2025)
Devon 1 is a high-yielding soybean variety with high isoflavone content. To increase the growth and yield of Devon 1 soybean variety, the use of environmentally friendly    fertilizers is needed. This study aims to determine the optimal combination of NPK fertilizer and mycorrhizal to increase the growth and yield of Devon 1 soybean variety. The research was conducted from October 2021 to January 2022 at Tri Dharma Experimental Farm, Faculty of Agriculture UGM, Banguntapan, Bantul, Yogyakarta. This study used a single factor randomized complete block design (RCBD) with three blocks as replications. The treatments were as follows: no fertilizer or control, 100% NPK, mycorrhizal, 25% NPK + mycorrhizal, 50% NPK + mycorrhizal, and 75% NPK + mycorrhizal. The results showed that the treatment combination of 75% NPK + mycorrhizal produced the highest leaf area and shoot dry weight at six weeks after planting, the highest seed yield (3.16 t.ha-1), and the highest flavonoid content (367 μg.g-1).